(untitled) (قضايا سياسية, 2024)
The researcher deals with the importance of the Middle East from a geopolitical perspective for the world powers, and the most important conflicts in contemporary international issues in our modern era, and aims to show the reality and role of the United States of America in the Israeli-Palestinian conflict. The future of the Palestinian cause in light of weakness and the Arab state of laxity. By following different research methods "descriptive analytical based on analysis and conclusion, investigation and descriptionIt concluded that the Middle East complex lies in a geopolitical struggle between colonial powers and great powers. The United States is part of the Palestinian problem because of the clear bias towards Israel and its political, economic and military support. Arab weakness negatively affects the Palestinian position. The effectiveness of student movements in Western universities. Official and popular public opinion sympathized with the Palestinian narrative and cause. Islam is the only threat to the world order" factorization. The war on Gaza has weakened the paths of normalization. The case was reinstated to be among the priorities of the international community. The study came out with some recommendations, the most important of which is to end the Palestinian-Palestinian division.